A Clinical Study to Evaluate the Effect of Vaman Karma in Vasant Ritu in Healthy Individuals - Diksha Sharma; Charu Supriya; Vijay Chaudhary (AYUSHDHARA, 2025)
Panchkarma is an indispensable part of the Ayurveda. It covers all imperative aspect of treatment that is preventive, preservative, promotive, curative, and rehabilitative by means of five major procedures like Vaman, Virechana, Niruha basti, Anuvasan basti and Nasya and many allied therapies. In the present research work an effort has to be made to establish effect of Vaman karma on naturally vitiated Kapha in study subject. Objective: A clinical study to evaluate the effect of Vaman Karma in Vasant Ritu in healthy individuals. Methodology: In the present study total 100 individuals were selected and randomly divided as 50 individuals in each group. In interventional group 50 individuals were administered Vaman Karma in Vasant Ritu and observed for two consecutive months for good health profile i.e., reduction in Kapha Vriddhi Lakshan. and in observational group 50 individuals were taken and they were observed for two months for reduction in Kapha Vriddhi Lakshan. Result: In Group A (Interventional Group) marked reduction in Kapha Vriddhi Lakshan was seen as compared to Group B (Observational Group). Conclusion: During study it was observed that Vamana Karma, when performed in the early hours, in the morning on noncloudy sunny day it gave better results and study subjects performed the Karma comparatively in an easy way and Doshas were expelled out in much more quantity, usually without giving any discomfort and complications to the study subjects.